Archaeology of daily life: ordinary persons in late Second Temple Israel - Fiensy, David A. (Cascade Books, 2020)
What were the climate and topography of Palestine/Israel? -- What was city life like? -- what was village life like? -- What kind of house would you have lived in? -- What would your family dynamic have been life? -- What would be inside your house? -- What would you do for a living? -- What would your bones tell us? -- What chronic disease(s) would you probably have contracted? -- How long would you have lived? -- How and where would they bury you? -- How would you practice your religion?